2001
DOI: 10.1007/s100160010002
|View full text |Cite
|
Sign up to set email alerts
|

The Value and Limitations of the Arm Cephalic and Basilic Vein for Arteriovenous Access

Abstract: The National Kidney Foundation has identified the use arteriovenous grafts (AVG) and the interventions required to maintain their patency as two major causes of increased expenditure in the management of hemodialysis access in end-stage renal disease patients. They have issued an appeal for the increased use of native arteriovenous fistulae (AVF). Although the radialcephalic AVF is considered to be the procedure of choice for these patients, other veins should be sought after to maintain an all-autogenous AVF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
8
0
6

Year Published

2003
2003
2013
2013

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 18 publications
2
8
0
6
Order By: Relevance
“…History of previous failed dialysis access was another factor that adversely influenced primary and secondary patency. This finding has been demonstrated by other authors 28,34 and may be related to yet undefined patient factors such as propensity to intimal hyperplasia. Age, gender, and diabetes did not exert an effect on patency in our or other series.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…History of previous failed dialysis access was another factor that adversely influenced primary and secondary patency. This finding has been demonstrated by other authors 28,34 and may be related to yet undefined patient factors such as propensity to intimal hyperplasia. Age, gender, and diabetes did not exert an effect on patency in our or other series.…”
Section: Discussionsupporting
confidence: 55%
“…16,29 Increased age 20,29 and presence of diabetes 20 have also been associated with decreased prevalence of fistula use. Furthermore, age, 13,19,31 diabetes, 1,10,32 female gender, 1,33 and history of previous failed dialysis access 7,28,34 have been shown to predict access failure. In order to limit the effect of these confounding factors on outcomes, we performed case matching of our tAVF and AVG groups to control for age, gender, race, diabetes, and history of previous failed access and then used multivariate regression techniques to assess outcome differences between the two procedures.…”
Section: Discussionmentioning
confidence: 97%
“…Patients with multiple previous fistulas are also more likely to be exposed to frequent upper extremity central venous catheterization attempts, which may lead to central venous outflow obstruction eventually leading to fistula failure. 14,18 Vein size may also be an important factor for fistula patency as it has been previously proposed that larger vein size is associated with better patency. Hill et al reported that at a mean follow-up of eight months, the primary patency rate of AVFs in patients with basilic vein diameters of four mm or more on preoperative duplex ultrasonography was 80%, versus 50% for those with vein diameters less than four mm.…”
Section: Discussionmentioning
confidence: 96%
“…3,6,9,10,14 In addition, there are limited data from randomized prospective studies in the literature, further restricting its widespread application. 6 In this prospective randomized study, we compared the outcomes of BCAVF and BBAVF in order to determine whether selecting one type of vein is superior in terms of patency and complications.…”
Section: Discussionmentioning
confidence: 99%
“…4 Consistent with other studies, TBBVFs outperformed the other AVF types; excellent maturation rates with this type of AVF have been reported. 21,26 Interestingly, total usage and/or release rate of AVFs and AVGs did not change at all during the course of the study. We believe that this observation reflects the presence and use of adequate venous outflow, which most likely did not change throughout the study.…”
Section: Discussionmentioning
confidence: 92%